Gambaran Demografi Pola Makan Dan Tingkat Stres Penderita Hipertensi Usia Produktif Di Puskesmas Kartosuro Sukoharjo - WAHYU SUBKHI, Wahyu SUBKHI; , Abi Muhlisin, SKM, M.Kep; , Dewi Listyorini, S.Kep., Ns (2016)
DEMOGRAPHIC OVERVIEW OF DIET AND STRESS LEVEL OF YPERTENSION PATIENTS AGED PRODUCTIVE IN HEALTH KARTOSURO SUKOHARJO By: Wahyu Subkhi Hypertension is a major health problem throughout the world because the high prevalence and associated with an increased risk of cardiovascular disease. Hypertension trigger factors can be distinguished on that can not be controlled (such as heredity, gender, and age) and that can be controlled (such as obesity, lack of exercise, smoking, and alcohol consumption and salt). This study aims to find out find a picture of hypertensive patients of childbearing age in public health center of Kartosuro. This research is descriptive analytic. The study population is hypertensive Kartasura productive age in the health center in January 2014, amounting to 544 patients. Sample study of 110 hypertensive patients of reproductive age with simple random sampling technique.Gathering data using questionnaires. Data were analyzed using univariate test. The study concluded that (1) an overview of factors family history of hypertension productive age most have a family history of suffering from hypertension, (2) description of body weight hypertensive patients of childbearing age are mostly normal and obesity, (3) description of patients with hypertension diet most of the productive age is moderate, and (4) a description of stress levels in hypertensive patients of childbearing age at public health center of Kartosuro Sukoharjo mostly mild stress. Keywords: amily history, weight, diet, stress levels, people with hypertension, the productive age